Reconstruction of "berkah jaya bake house" marketing strategy for consumer visiting interest - Shabrina, Fitriatunnisa; Fitriyana, Dian; Jaya, M. Abin; Irawan, Joseph Aldo (Journal of Gastro Tourism, 2024)
The fact that marketing continues to evolve towards digital dynamics, E-WoM is present as a key element in the latest marketing strategies. This study will provide a brief overview of E-WoM as a natural form of marketing carried out by consumers and how optimized marketing strategies can benefit from it. The study focuses on studying the impact of the spread of E-WoM on consumer visiting interest and aims to examine the role and impact of E-WoM management on consumers. The qualitative approach is carried out by the author with case studies, field studies, to literature studies assisted by documentation and interview methods. The data analysis model is drawn conclusions with a data triangulation model. In the process of using social media, berkah jaya bake house seems to rarely post pictures, but still has high polularity due to the influence of E-WoM. Planning for the reconstruction of the E-WoM marketing strategy is carried out at the locus of "Berkah Jaya Bake House", especially through social media accounts.